The work design contribution to educational workers' sustainable wellbeing and performance patterns - Pérez-Nebra, Amalia Raquel; Viana, Brenda Soares; Lira, Eva; Martín-Hernandez, Pilar; Gracia-Pérez, María Luisa; Gil-Lacruz, Marta (Frontiers in Psychology, 2022)
Brazilian education faces difficulties with performance and illness suggesting that the characteristics of the work can affect both variables. This study aims to describe the work characteristics that increase the odds of being in the happy-productive patterns of education workers. A total of 4,598 employees of the Secretariat of Education of the Federal District (SEEDF) participated in the research, answering questionnaires about work design (Brazilian version, with 18 factors), well-being (containing 3 factors) and performance. The results showed that task, social, and contextual characteristics increase the probability of being in the happy-productive pattern, and specifically, Social Support, Feedback from Others, Task Significance, Task Identity, and Autonomy, in this order, should be considered for intervention purposes.